Acute Pancreatitis Following Organophosphate Compound Poisoning: A Case Report. Issue 4 (2021) - Jha, Suman K.; Chaulagain, Sabin; Ojha, Shiva Kumar; Basnet, Angela; Sunuwar, Neela; Khadka, Akanchha
No abstract available